Penerapan Metode Pembelajaran Kooperatif Tipe STAD pada Siswa Kelas VII A SMPN 2 Kumai: The Application of STAD-Type Cooperative Learning Methods in Class VII A Students of SMPN 2 Kumai - Rustianingsih, Rustianingsih (Anterior Jurnal, 2022)
To increase the participation and learning outcomes of Civics, the learning must be interesting, so that students are motivated to learn. This form of research is reflective by taking certain actions in order to improve and improve learning practices in the classroom. The subjects of this study were students of class VII A of SMPN 2 Kumai whose active participation and learning outcomes in Civics subjects were still low or less than 75 according to the minimum learning completeness standard (SKBM). The results showed that the application of the STAD type cooperative learning method in Civics subjects could increase active participation and student learning outcomes.